2006
DOI: 10.1007/s00423-006-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Systemic capsaicin inhibits neuronal activation in the brainstem during postoperative ileus in the mouse

Abstract: The inhibition of capsaicin-sensitive vagal afferent pathways appears to boost rather than to attenuate the inflammatory response during postoperative ileus, while intestinal motility remained unchanged. This suggests a protective role of the capsaicin-sensitive afferent innervation for the inflammatory phase of postoperative ileus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…This would be in keeping with the increased inhibitory EFS-response in P12h in our EFS-studies exploring the effect of endogenously released VIP. As previously shown in our studies 24 h after induction of POI, 20,21 we were now able to demonstrate also an early (12 h) and late (3 days) activation of vagal afferent pathways during POI, reflected by increased c-fos expression in the NTS. However, while Boeckxstaens and colleagues demonstrated that intestinal manipulation causes an inhibition of intestinal motility via a vagal reflex pathway involving inhibitory NANC neurotransmitters, such as VIP, 3,52 we were unable to find an increased c-fos expression in the DMV representing the root of the efferent limb of the vagal reflex.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This would be in keeping with the increased inhibitory EFS-response in P12h in our EFS-studies exploring the effect of endogenously released VIP. As previously shown in our studies 24 h after induction of POI, 20,21 we were now able to demonstrate also an early (12 h) and late (3 days) activation of vagal afferent pathways during POI, reflected by increased c-fos expression in the NTS. However, while Boeckxstaens and colleagues demonstrated that intestinal manipulation causes an inhibition of intestinal motility via a vagal reflex pathway involving inhibitory NANC neurotransmitters, such as VIP, 3,52 we were unable to find an increased c-fos expression in the DMV representing the root of the efferent limb of the vagal reflex.…”
Section: Discussionsupporting
confidence: 86%
“…18 To stain MPOpositive cells, fixed whole mounts were incubated for 10 min in a 1 : 10 dilution of 10 mL KRB, containing 10 mg Hanker-Yatesreagent (Polysciences, Warrington, PA, USA) and 100 ll hydrogen peroxide. 20 Mast cells were stained by overnight incubation with fluorescein isothiocyanate-avidin (1 : 10 in 10% normal horse serum) at 4°C followed by washouts in PBT. 4 Staining of macrophages was performed by preincubation in 5% normal donkey serum, followed by incubation with the primary antibody (ED2, mouse antirat CD 163; Abd Serotec, D€ usseldorf, Germany; 1 : 100 in PBT with 2.5% NDS), washouts in PBT, and incubation with the secondary antibody (donkey antimouse; Millipore, Temecula, CA, USA; 1 : 500 in PBT).…”
Section: Histochemistry and Immunohistochemistrymentioning
confidence: 99%
“…On the other hand, physical vagotomies block the behavioral responses to an oral C. jejuni inoculation (Fleshner et al, 1995; Goehler et al, 1995; Watkins et al, 1995; Fleshner et al, 1997; Fleshner et al, 1998; Goehler et al, 1998), thus suggesting that the vagus nerve is the relevant neuronal pathway communicating intestinal challenges to the nTS. Additionally, Mueller et al (Mueller et al, 2006) have shown that inflammation induced by intestinal manipulations during surgery is also capable of inducing c-Fos-ir in the brainstem via a pathway sensitive to capsaicin treatments. Our results now show that irritation caused by bacterial agents appears to activate a similar population of neurons as physical manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, selective ablation of afferents by capsaicin was tested in a previous study at the 24-h time point and did not show any effect on motility compared to controls. 24 We, therefore, believe that it is very unlikely that vagal efferent or afferent fibers contribute selectively to the early inhibition of intestinal motility brought on by spinal reflexes. 8 This study supports current understanding of postoperative ileus as a condition consisting of two phases.…”
Section: Discussionmentioning
confidence: 99%